A Qualitative Examination of Second Grade Teachers' Experiences and Attitudes Around Coding and Robotics Education - Govind, Madhu. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Marina Bers.; Committee: Christine McWayne, Christine Wang, and Rebecca Dore.; Keywords: Educational technology, Computer science, and Elementary education.